THE EFFECT OF READING STRATEGIS AND LEARNING STYLES ON THE STUDENTS ACHIEVEMENT IN READING COMPREHENSION - Afdhalina Afdhalina (Jurnal Scientia, 2022)
The objectives of this study are to find out whether or not: (1) students’ achievement in reading ccomprehension taught by INSERT strategy is significantly higher than QAR strategy, (2) students’ achievement in reading comprehension those who have visual learning style higher than those who have auditory learning style, (3) there is interaction between reading strategies and learning styles on students’ achievement in reading comprehension. An experimental research with factorial design 2 x2 was used in this study. There were 120 students from the academic year of English Department (Tadris English) STAIN Gajah Putih Takengon in Central Aceh taken as the sample of this research. The students were divided into two groups. The first group was treated by using INSERT strategy and the second group was treated by QAR strategy. Learning styles was measured by giving the questionnaire for classifying the students that have visual and auditory learning style. Students’ achievement in reading comprehension was measuring by given essay and multiple choice test. The data were analyzed by applying Two-Way ANNOVA. The result reveals that (1) students’ achievement in reading comprehension taught by INSERT (X=30.23) is significantly higher than students’ achievement in reading comprehension taught by by QAR (X=27.20) with Fobserve=15.70 > Ftable=3.92 at the level of significant α=0.05, (2) students’ achievement in reading comprehension who have visual learning style (X=26.17) is higher than students’ achievement who have auditory learning style (X=24.83) with Fobserve=7.12 > Ftable=3.92 at the level of significant α=0.05, (3) there is significant interaction between reading strategies and learning styles on students’ achievement in reading comprehension with Fobserve=12.07 > Ftable=3.92. After the Tuckey Test was applied, it showed that the students who have visual learning style got higher result if they were taught by using INSERT strategy and students who have auditory learning style got higher result if they were taught by QAR strategy.